Vulnerability, Trustworthiness, and Motivation as Emergent Themes in Cooperation With Community-Based Water Management in Southwestern Uganda - Hamm, Joseph A.; Pearson, Amber L.; Namanya, Judith; Gore, Meredith L. (Frontiers in Environmental Science, 2020)
Discipline and context specific inquiries into the nature and dynamics of trust are beginning to give way to cross-boundary understandings which seek to outline its more consistent elements. Of particular note within these is an argument that trust is premised on vulnerability; that it has an important nexus with assessments of the ability, benevolence, and integrity of the trust target; and that it can also be motivated. The current work seeks to shed preliminary light on the applicability of this argument to a context in which it has not previously been examined: community-based water management in southwestern Uganda. Using a deductive, theory-driven analysis of focus group discussions with residents, we show that when our participants were simply asked to discuss their relationships with local management committees, vulnerability, ability, benevolence, and integrity consistently emerged as salient themes. Motivation, however, emerged as most salient for women. Further analysis suggests that this may have been because women are more directly involved in water provision, thereby increasing their perceived need for the resource. Our results, therefore, lend credence to the cross-boundary nature of this increasingly nuanced theoretical understanding of trust but also suggest some general guidance for improving community-based resource management efforts by providing preliminary evidence regarding the relative roles of trustworthiness and motivation.